POTENSI PAKANTrigona spp. DI HUTANLARANGAN ADAT DESA RUMBIO KABUPATEN KAMPAR - Septian Hardi Yanto; Defri Yoza; Evi Sri Budiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Indonesia is tropical country that have abundant of natural resources of flora and fauna.One fauna that are useful for human is honeybees.Traditional forest the prohibition rumbio kampar regency a potential to cultivation development honeybees. In the forest ban customary rumbio a lot of there are honeybees kind of trigona spp.( klanceng ) where a product produced trigona spp. Namely honey and propolis. Besides used to health honey and propolis of trigona spp . It has the selling price far higher than with honey will not be used as additional income for the local community . This study aimed to examine the potential feed and crop a source of feed trigona spp . In the woods ban rumbio kampar Regency.The method that used in this research is the procedure of making a sample plot. Plot made in the form of a circle of 0.10 ha with the fingers 17,8 meters. Intensity of sampling used is 1 percent , so extensive sample being observed is 1.54 ha. The plot observed some 1,54 ha ha divided by 0,10, there are 16 plot. Distance between a sample plot in a line that is 100 meters. The results indicated that potential feed on the highest trees kempas (koompassia malaccensis) with the smallest 30,27 % and is trees kelatmerah (syzygium sp) worth 4,98 %. Feed bees trigona spp . At the ban village forest customary rumbio district kampar available every years , although as the quality has variance month to month. Keywords: Trigona spp.,Traditional Forest the Prohibition, feed.